091 Evaluation of remote assessments for multiple sclerosis in a real-world setting. Issue 6 (27th May 2022) - Kuri, Ashvin; Jacobs, Benjamin Meir; Leddy, Sara; Schmierer, Klaus; Turner, Benjamin; Allen-Philbey, Kimberley; Stennett, Andrea; Giovannoni, Gavin; Thomson, Alison; Dobson, Ruth
Abstract : Background: There is an urgent need for reliable methods to remotely monitor Multiple Sclerosis (MS). Existing assessments, such as Timed 25-Foot Walk (T25FW) and 9-Hole Peg Test (9HPT), are traditionally carried out in person by physicians. The use of self-administered, remote versions of these assessments could improve monitoring and hence care for people with MS (pwMS). This study evaluated the use of remote T25FW (rT25FW) and 9HPT (r9HPT) assessments. Methods pwMS were given comprehensive instructions and equipment for completing rT25FW/r9HPT. We assessed relationships between EDSS scores (through a previously-validated webEDSS) and contem- poraneous rT25FW/r9HPT using Spearman's rank-order correlation, to evaluate consistency with previous in-person studies. Results: Seventy-one pwMS completed the webEDSS and r9HPT, and 108 completed the webEDSS and rT25FW. There was a mild-moderate positive correlation between webEDSS and rT25FW (rho=0.40, p<0.0001, 95%CI=0.23–0.55), a finding consistent with previous in-person studies. There was a non-significant weak correlation between webEDSS and r9HPT. Distributions of rT25FW/r9HPT times were positively skewed. 100% of r9HPT times and 93.5% of rT25FW times were within specified limits used in clinical trials. Conclusion: These findings provide pilot evidence to indicate remote monitoring of MS is feasible. These assessments should be further developed to aid remote follow-up of pwMS. ashvin.kuri99@gmail.com